2019
DOI: 10.1111/cns.13249
|View full text |Cite
|
Sign up to set email alerts
|

Early elevated neutrophil‐to‐lymphocyte ratio associated with remote diffusion‐weighted imaging lesions in acute intracerebral hemorrhage

Abstract: Aims To explore the relationship between the circulating neutrophil‐to‐lymphocyte ratio (NLR) and the remote diffusion‐weighted imaging lesions (R‐DWILs) after spontaneous intracerebral hemorrhage (ICH). Methods Consecutive patients with spontaneous ICH were prospectively collected from November 2016 to May 2018 and retrospectively analyzed. We included subjects who presented within 24 hours after symptom onset and were free of detectable infections on admission or in hospital. Blood samples were obtained at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Our results showed that the cerebral infarction group had higher NLR than the non-cerebral infarction group. A previous study revealed that early elevated NLR was associated with remote DWI(+) lesions in acute intracerebral hemorrhage (32). It is well established that inflammation is acutely involved in the process of ischemic stroke (33).…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that the cerebral infarction group had higher NLR than the non-cerebral infarction group. A previous study revealed that early elevated NLR was associated with remote DWI(+) lesions in acute intracerebral hemorrhage (32). It is well established that inflammation is acutely involved in the process of ischemic stroke (33).…”
Section: Discussionmentioning
confidence: 96%
“…Iron overload during the process of Ang II‐induced hypertension might exacerbates brain injury after ICH by inflammatory activation. Both ICH‐related systemic inflammation 44 , 45 and microglia/macrophage‐mediated inflammation activation 46 play an important role in brain injury, recovery, and stroke outcome. In our study, increased vascular inflammation (indicated by MCP‐1‐and Mac2‐positive cells and IBA‐1 positive cells) were observed in Ang II‐infused mice, while, iron chelation decreased inflammatory activation and secondary bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload during the process of Ang II-induced hypertension might exacerbates brain injury after ICH by inflammatory activation. Both ICH-related systemic inflammation 44,45 and microglia/macrophage-mediated inflammation activation 46 play an important role in brain injury, recovery, and stroke outcome. In In addition, after ICH modeling, we observed obvious accumulation of astrocytes, the inhibition of which has been reported to decrease HE and BBB destruction in collagenase-induced ICH rats.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Previous prospective studies have shown that elevated admission WBC count and neutrophil count are associated with an increased risk of early neurologic deterioration in ICH [37][38][39] as well as in ischemic stroke. 40 Multiple studies have also reported increased neutrophil-to-lymphocyte ratio associated with higher mortality and increased intracerebral remote diffusion-weighted imaging lesions in ICH, 41,42 and worsened prognosis in glioma. 43 Although the Multiple prospective investigations have indicated that achieving early and stable blood pressure seems safe and associated with favorable outcomes in acute ICH patients.…”
Section: Discussionmentioning
confidence: 99%